Image process device and the operation method - LEE JAE LIN; JEON BYEUNG WOO (2023)
An image processing device is provided that includes: a plurality of light sources for emitting a plurality of lights, respectively; a camera for outputting an image of a first subject obtained by photographing a subject; and a control parts that controls each of the plurality of light sources according to a light code pattern set set based on a complex modulation transfer function during the shutter exposure time of the camera, and outputs a second subject image in which motion blur is removed from the first subject image according to a point spread function for each color channel modulated by the light code pattern set. Thus, it is possible to easily output a clear second subject image. 본 발명은, 복수의 광을 각각 발산하는 복수의 광원, 피사체를 촬영한 제1 피사체 영상을 출력하는 카메라 및 상기 카메라의 셔터 노출 시간 동안, 상기 복수의 광원 각각을 복합 변조전달함수를 기반으로 설정한 광 코드 패턴 세트에 따라 제어하며, 상기 광 코드 패턴 세트에 의해 변조된 색상 채널별 점확산 함수에 따라 상기 제1 피사체 영상에서 모션블러가 제거된 제2 피사체 영상을 출력하는 제어부를 포함하는 영상 처리 장치를 제공한다.